Prodiplosis longifila Gagné (Diptera: Cecidomyiidae) in asparagus (Asparagus officinalis) crop in Chavimochic Irrigation Project - Castillo Valiente, Jorge Ramón (2020)
The present study was conducted in the fields of the Chavimochic irrigation, located in La Libertad Region-Peru. Prodiplosis longifila Gagné (Diptera Cecidomyiidae) is considered the key pest of asparagus and other vegetables cultivation. This study aimed to characterize the presence of this insect pest in asparagus crop under drip irrigation conditions, in order to find the best alternatives for its control. The cultivar most planted in the Chavimochic Irrigation is cultivar UC 157 and that the meteorological conditions of the area are optimal for the production of asparagus; but also for the establishment and reproduction of the insect. The morphology of asparagus is favorable for reproduction of the insect, from larva to adult, since it frequently bracts and flowers at larval stage and establishs itself at the adult stage; at the base of the plant. All experiments conducted, had at least three repetitions and the results are given on average. The insect can have many hosts and an average biological cycle of 11 days, with the highest populations in the months of May and November. Throughout the day; the adult populations are very active from 10 pm to 4 am. The drip irrigation system provides better conditions for the establishment of the insect and its reproduction in the fields, as well as the design of double row sowing so water management becomes an important factor for managing its populations. From the 100% puparium that fell to the ground, only 37.95% emerged as adults. The percentage of damaged stems per linear meter can be 70.46 and healthy stems 29.54. The number of larvae per shoot can be from 68 to 489 while number of larvae per male flower can be from 2 to 7 individuals. There is a relationship between flowering and the number or pre-pupae fallen to the ground, but as the crop develops, the adult´s number decrease, but nevertheless is still aggressive and permanent.